Selected orthographic features in English editions of the Book of good maners (1487-1507) - Rutkowska, Hanna (Sociedad Espanola de Lengua y Literatura Inglesa Medieval, 2005)
In this paper I discuss the results of my research on the orthography in selected late fifteenth- and early sixteenth-century books printed in English. I compare the spelling systems of three printers: William Caxton, Richard Pynson and Wynkyn de Worde as apparent in several editions of Caxton’s translation of Le livre de bonnes moeurs, published in 1487 as the Book of good maners.
Keywords: ortografia; orthography; pisownia; spelling; Anglia; England; drukarze; printers; język wczesny nowoangielski; Early Modern English